Organophosphorus pesticides toxicity on brine shrimp artemia - Ali, Jawahar; Mohamed, A. Jamal; Kumar, M. S. Arun; John, Akbar (Zibeline International Publishing, 2018)
Present investigation discusses the toxic effects of two organophosphorus pesticides (Malathion) and (Glyphosate) on brine shrimp, Artemia in static acute toxicity tests (24hr and 48hr). Toxicity tests were performed at a temperature of 27±1⁰C with a photoperiod of 12h light and 12h dark. Ten healthy nauplii were exposed to five different concentrations of Malathion (10, 20, 40, 60 and 80 ppm) and Glyphosate (0.01, 0.02, 0.03, 0.04 and 0.05 ppm) along with a control group. Finney’s Probit analysis was used to determine the 24h/48h LC50 values and were found to be 58.3 and 17.3 ppm, 0.028 and 0.019 ppm for Malathion and Glyphosate, respectively. Of the two pesticides tested Glyphosate was found to be significantly more toxic to Artemia nauplii than that of Malathion (P < 0.05).